DYNAMIC CHARACTERISTICS AND DYNAMIC RESPONSE ANALYSIS OF THREE STOREY GARAGE ON THE DYNAMIC CHARACTERISTICS OF THE GARAGE - XIE Miao; HUANG YaXing; LIU ZhiXiang; MAO Jun; TONG Yang (Jixie qiangdu)
In order to study the stereo garage frame structure stability and displacement of frame under earthquake load response,combined with the theory of modal analysis and extraction method,using ANSYS finite element software to frame modal calculation,and extract the natural frequencies and mode shapes of order 8 of its former. The EI Centro earthquake wave which is similar to the seismic requirements has been chosen for simulated seismic wave which is used to analyze the deformation of the frame. The results show that the natural frequency of the frame is lower,and the resonance phenomenon may occur due to the external load. The frame natural frequency should be avoided similar to the external load vibration frequency. The displacement response of each frame node under the action of simulating seismic waves is between- 30 mm 35 mm,and the value is far less than the material yield limit. That suggests the seismic performance of three-dimensional parking spaces can meet the requirements.